The effectiveness of blood-flow restricted resistance training in the musculoskeletal rehabilitation of patients with lower limb disorders: A systematic review and meta-analysis. (September 2021) - Nitzsche, Nico; Stäuber, Alexander; Tiede, Samuel; Schulz, Henry
Objective: This meta-analysis aimed to evaluate the effectiveness of low-load Resistance Training (RT) with or without Blood Flow Restriction (BFR) compared with conventional RT on muscle strength in open and closed kinetic chains, muscle volume and pain in individuals with orthopaedic impairments. Data sources: Searches were conducted in the PubMed, Web of Science, Scopus and Cochrane databases, including the reference lists of randomised controlled trials (RCT's) up to January 2021.Review method: An independent reviewer extracted study characteristics, orthopaedic indications, exercise data and outcome measures. The primary outcome was muscle strength of the lower limb. Secondary outcomes were muscle volume and pain. Study quality and reporting was assessed using the TESTEX scale. Results: A total of 10 RCTs with 386 subjects (39.2 ± 17.1 years) were included in the analysis to compare low-load RT with BFR and high or low-load RT without BFR. The meta-analysis showed no significant superior effects of low-load resistance training with BFR regarding leg muscle strength in open and closed kinetic chains, muscle volume or pain compared with high or low-load RT without BFR in subjects with lower limb impairments. Conclusion: Low-load RT with BFR leads to changes in muscle strength, muscle volume and pain in musculoskeletal rehabilitation that are comparable to conventional RT. This appears to be independent of strength testing in open or closed kinetic chains.